Hej!
a)
-11(x - 2y) + 2x = -11x + 22y + 2x = -9x + 22y
b)
8 - 20 + 44 = -12 + 44 = 28
c)
-9a - (3a + 6) + 7(8 + a) =
= -9a - 3a - 6 + 56 + 7a = -2a + 50
d)
10 + 3a - 2(-5 + a) = 10 + 3a + 10 - 2a =
= a + 20
e)
-2(2c + 6) + 4(8 - b - 4c) =
= -4c - 12 + 12 - 4b - 16c = -4b - 20c
f)
-(3a - c) + 2a - (2c - 3a) + (2c - a) =
= -3a + c + 2a - 2c + 3a + 2c - a =
= a + c
g)
9(x - y) - 9y - 5(y - x) + x =
= 9x - 9y - 9y - 5y + 5x + x =
= 15x - 23y
h)
10 - [4 - (a + 5) + 3a] * 5 =
= 10 - (4 - a - 5 + 3a) * 5 =
= 10 - (2a - 1) * 5 = 10 - 10a + 5 = -10a + 15
Pozdrawiam! - Julka